2000
DOI: 10.2460/javma.2000.217.874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a static magnetic field on blood flow to the metacarpus in horses

Abstract: Results suggest that in horses, the static magnetic field associated with application of commercially available magnetic wraps for 48 hours does not increase blood flow to the portion of the metacarpus underneath the wrap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…However, our results are supported by studies in humans that report no changes during exposure to magnets with strengths less than 1 T in both muscle and skin blood flow at rest (20,23) and during deep inspiration (22). Likewise, wrapping the metacarpus region of the horse with 0.027-T magnets did not alter blood flow in that region (32). The finding of the present study supports the conclusion that exposure to static magnetic fields, at the strength commonly used in nominally therapeutic devices, do not elicit changes in local blood flow, blood pressure, or heart rate in humans at rest or during physiological stress.…”
Section: Discussionsupporting
confidence: 86%
“…However, our results are supported by studies in humans that report no changes during exposure to magnets with strengths less than 1 T in both muscle and skin blood flow at rest (20,23) and during deep inspiration (22). Likewise, wrapping the metacarpus region of the horse with 0.027-T magnets did not alter blood flow in that region (32). The finding of the present study supports the conclusion that exposure to static magnetic fields, at the strength commonly used in nominally therapeutic devices, do not elicit changes in local blood flow, blood pressure, or heart rate in humans at rest or during physiological stress.…”
Section: Discussionsupporting
confidence: 86%
“…There is additional evidence that the applications of moderate, strong, and ultrastrong intensity SMF ranging 1 mT-8 T to healthy subjects and animals mask hemodynamic effects. These SMF intensities exhibited no significant effects on BP, SBF or locomotor activity in healthy humans or animals up to 8 T [Battocletti et al, 1981;Tenforde et al, 1983;Davis et al, 1984;Willis and Brooks, 1984;Barker and Cain, 1985;Mészáros, 1991;Stick et al, 1991;Kangarlu et al, 1999;Steyn et al, 2000;Mayrovitz et al, 2001Mayrovitz et al, , 2005Hinman, 2002;Martel et al, 2002;Tenforde, 2005]. These studies, including our own, provide evidence that normal cardiovascular system and locomotor activity are not easily affected by moderate-intensity SMF.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, our series of studies (Ohkubo and Xu 1997;Xu et al 1998Xu et al , 2000Okano et al 1999Okano and Ohkubo 2001, 2003a, b, 2005a, b, 2007Gmitrov et al 2002;Gmitrov and Ohkubo 2002a, b) and other independent studies (Prato et al 1990;Steyn et al 2000;Mayrovitz et al 2001Martel et al 2002;Morris and Skalak 2005Kuipers et al 2007;Li et al 2007;Kim et al 2010), as shown in Table 1, have demonstrated that hemodynamics and/or BP were modulated by moderate intensity SMF in mT level fields in pharmacologically treated animals and genetically hypertensive animals, while there was no change in normal, conscious animals when the values of the BP were within normal range (reference values). Therefore, we concluded that significant bioresponses to therapeutic signals occur when the deviations of the endpoints are far from homeostasis.…”
Section: Discussionmentioning
confidence: 95%